Modification of the Integrated Agro-Waste-Based Palm Oil with PET for Wastewater Treatment - Suradi, Siti Samahani; Afiq Zikri Zool Pakar,; Rahman Hamimi Abd Hamid, (Multidisciplinary Applied Research and Innovation, 2024)
The most common reusable resources in Malaysia are waste based palm oil plants: Empty fruit bunches, fiber and palm kernel shell which are all by-products from palm oil mills. This resource is classified as agro-waste and exhibits great potential to be used as a filter media for wastewater treatment applications. In this study, the selected polyethylene terephthalate (PET) flat sheet was treated with sodium hydroxide (NaOH) and coated with calcinated waste-based palm oil with the immersion of polyvinyl fluoride (PVDF) and dimethylformamide (DMF) by using the dip-coating method. This integrated composite is applied to analyze the performance of the color of palm oil final treated effluent based on the calcination temperature of 500°C. Characterization of samples was conducted by Scanning Electron Microscopy (SEM) and Fourier Transformed Infrared Spectroscopy (FTIR) mainly to identify the morphology of the waste-based palm oil after calcination as well as determine the functional groups and chemical bonds that were involved. It can be seen morphologies and chemical structures between EFB, fiber, and PKS are different patterns. The reduction of the color value of effluent showed the hydrophobicity of the integrated palm oil waste coated with PET which enables to trap of the particles in the effluent, thus this composite has potential use in the filtration of water treatment. This preliminary study also showed that it requires further research, as the ability of the sample to use the dip-coating method to reduce the color of effluent showed potential for further use.